Solar Cell Motorcycle’s Parking Security System - Wan Abdullah, Wan Zaimi Bin (Universiti Teknologi PETRONAS, 2009)
This project is about a solar cell motorcycle’s parking security system. The objective of this project is to design and construct a solar power system for supplying the power to the motorcycle’s parking security system. Before this, the motorcycle’s parking security system was supplying by electrical energy. This is not so efficient and not applicable if the system only depending on that source. In this problem, the solar energy has advantages because sun will be around for all the time. The scopes of study in this project are to understand the working of solar system, analysis the factors that need to be considered in the project, design and implement a solar system on the motorcycle’s parking security system. The methodology is a project management process. This includes the project flow from the selection topic to construct the prototype and the final product desired. It also contain the duration of each step to archive the desired product. The expected outcome from this project is the solar power supply to motorcycle’s parking security system.